Endometriosis in pre- and perimenopausal age – how to treat? - Spaczyński, Robert Z.; Mitkowska, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2011)
Endometriosis, i.e. extragonadal localization of endometrial stroma and glands is predominantly found in reproductive age women, however it is also diagnosed in teenagers and postmenopausal women. Prevalence of postmenopausal endometriosis is 2-5% of all endometriosis cases, with majority found in patients using estrogen replacement therapy (ERT). Etiopathogenesis of endometriosis after menopause is related to extragonadal aromatase activity (androstendione to estradiol conversion). The aim of endometriosis therapy is to relief pain. This effect can be achieved either through pharmacological or surgical treatment. Majority of endometriosis medications relies on reduction of estradiol production. Combined hormonal contraceptive drugs (oral, transdermal, transvaginal) and gestagens constitute first-line pharmacological therapy. Second-line consists of GnRH analogs, intrauterine system releasing levonorgestrel, danazol, and gestrinone. Progressively more and more experimental treatments are applied in postmenopausal endometriosis, just to name aromatase inhibitors suppressing local estrogen production. Surgical therapy may be also considered as first-line approach. Depending on the history of illness, pain intensity, and patient expectations surgery can cover wide spectrum from local excision of endometriosis through interruption of neural pathways (presacral neurectomy) finishing with total hysterectomy with or without bilateral salpingoophoorectomy.